2022
DOI: 10.3390/antibiotics11070979
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Essential Oils Evaluated In Vitro against Escherichia coli and Staphylococcus aureus

Abstract: The spread of extended-spectrum β-lactamase-producing Escherichia coli and methicillin-resistant Staphylococcus aureus has caused a reduction in antibiotic effectiveness and an increase in mortality rates. Essential oils (EOs), known for their therapeutic efficacy, can be configured as novel broad-spectrum biocides. Accordingly, the bacteriostatic–bactericidal activity of Citrus Lemon (LEO), Pinus Sylvestris (PEO), Foeniculum Vulgaris (FEO), Ocimum Basilicum (BEO), Melissa Officinalis (MEO), Thymus Vulgaris (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…In this instance, the extract from Mitrephora thorelii should be noted for its bactericidal properties. [18,20]. Many experimental studies have shown a correlation between the antibacterial activity of plant extracts and secondary compounds found in plants [22].…”
Section: Discussionmentioning
confidence: 99%
“…In this instance, the extract from Mitrephora thorelii should be noted for its bactericidal properties. [18,20]. Many experimental studies have shown a correlation between the antibacterial activity of plant extracts and secondary compounds found in plants [22].…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers regarding the antifungal and antimycotoxicogenic potential of individual EOs of coriander, thyme, and oregano, it was highlighted the contribution of thymol and o-cymene as the major components in thyme EO, linalool in coriander EO, and carvacrol and o-cymene in oregano EO [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Other minor compounds, such as caryophyllene, β-myrcene, p -cymene, and γ-terpinene, were identified in the three analysed EOs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of TEO and the concentration to be used was based on its antimicrobial effect reported in the literature [ 49 ]. Commercially available natural TEO (Specchiasol S.r.l., Bussolengo, VR, Italy) stored in a brown glass bottle at the temperature of 0–4 °C was used in the experimental design.…”
Section: Methodsmentioning
confidence: 99%
“…Commercially available natural TEO (Specchiasol S.r.l., Bussolengo, VR, Italy) stored in a brown glass bottle at the temperature of 0–4 °C was used in the experimental design. The composition of TEO was confirmed by chromatography hyphenated with mass (GC/MS) technique [ 15 , 49 ]. To achieve the proper solubilization of TEO, suitable for all the experimental procedures, the mother solution was serially diluted in 5mL Brain Heart Infusion (BHI) (Oxoid, Milan, Italy) with 10% dimethyl sulfoxide (DMSO), obtaining solutions ranging from a concentration of 5% ( v / v ) to 1.25% ( v / v ), corresponding to 450–112.5 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation